Amazing glaze recipes and combinations : 200+ surefire finishes for low-fire, mid-range, and high-fire pottery - Kline, Gabriel, 1977- (Quarry, 2021)
"Get inspired and get glazing! Amazing Glaze Recipes and Combinations provides a captivating collection of sure-fire glaze recipes and electrifying combinations for low-fire, mid-range, and high-fire potters. Hundreds of photos and technically-edited recipes ensure you'll get the best possible results"--